Laboratory captivity can affect scores of metabolic rates and activity in wild brown trout. (10th December 2018) - Závorka, L.; Brijs, J.; Wengström, N.; Wallerius, M. L.; Näslund, J.; Koeck, B.; Aldvén, D.; Lassus, R.; Höjesjö, J.; Johnsson, J. I.; Cucherousset, J.
Abstract: Phenotypic scoring of wild animals under standardized laboratory conditions is important as it allows field ecologists and evolutionary biologists to understand the development and maintenance of interindividual differences in plastic traits (e.g. behaviour and physiology). However, captivity is associated with a shift from a natural familiar environment to an unfamiliar and artificial environment, which may affect estimates of plastic phenotypic traits. In this study, we tested how previous experience with laboratory environments and time spent in captivity affects behavioural (i.e. activity) and metabolic (i.e. standard and maximum metabolic rates) scoring of our model species, wild brown trout Salmo trutta . We found that individuals with previous experience of laboratory captivity (10.5 months earlier) showed higher activity in an open field test than individuals with no prior experience of laboratory captivity. Previous experience with captivity had no significant effect on metabolic rates. However, metabolic rates seemed to increase with increasing time spent in captivity prior to the collection of measurements. Although there are benefits of keeping wild animals in captivity prior to scoring, our results suggest that while allowing for sufficient acclimatization researchers should aim at minimizing time in captivity of wild animals to increase accuracy and ecological relevance of the scoring of plastic phenotypic traits. Abstract : Phenotypic scoring of wild animals in laboratory is important as it allows field ecologists and evolutionary biologists to study plastic traits (e.g. behaviour and physiology) in standardized conditions. However, captivity is associated with a shift from a natural familiar environment to an unfamiliar and artificial environment. We found that previous experience with laboratory environments increases activity and time spent in captivity increases metabolic rates of brown trout. Our findings suggest that researchers should aim at minimizing time in captivity while allowing for sufficient acclimatization of wild animals to increase accuracy of the scoring of plastic phenotypic traits.